Kako določiti dominantno nogo? - Besal, Sara (Šport (Ljubljana), 2022)
Leg dominance determination plays an important role in sports science, but there are still divided opinions about the true meaning of leg dominance and a correct way of its determination. Determination of leg dominance has a significant impact on optimal movement technique and interpretation of motor test results. Nevertheless, to date, there is no clear method to reliably determine the dominant leg for different movement tasks. The purpose of this article was to review the literature on reliably determining leg dominance for various movement tasks and to provide recommendations for determining leg dominance prior to testing various motor skills. After reviewing the literature, we found that methods for determining leg dominance fall broadly into five categories: stability and/or balance, push-off (vertical or horizontal component), manipulation, kicking, and strength dominance. This article presents eight tests selected for their accessibility, complexity of performance, and low time and energy requirements. The tests can be used to determine leg dominance prior to athletic skill training or motor skill testing in research. In the future, it would be necessary to standardize the testing procedures, which would allow generalization of the results of motor skill tests considering leg dominance.
Keywords: asimetrija; gibalne sposobnosti; noga; odriv; ravnotežje; raziskave; skoki; šport